Creep Lifetime Assessment of Pressure-Tight PE100 Pipes Based on a Slow Fatigue Crack Growth - Luo, W.B.; Liu, Y.P.; Yin, B.Y.; Li, Y.; Liu, X. (Проблемы прочности, 2018)
Polyethylene pipes are widely used in water supply, gas, and sewage systems due to their excellent mechanical properties. A slow crack growth is the primary fracture mechanism for the pipes under long-term internal pressures. If the creep loading is treated as a special case of fatigue loading, the slow crack growth kinetics of polyethylene is defined in fatigue fracture tests at different stress ratios and extrapolated to creep crack kinetics. Linear elastic fracture mechanics concepts became the basis for predicting the creep lifetime of pressure-tight pipes subjected to various hoop stresses from extrapolated (synthetic) creep crack growth curves, and the prediction is in good agreement with the standard extrapolation, in accordance with ISO 9080.